Front Matter of Buletin Pengabdian or Bulletin of Community Services (Bull. Community. Serv.) Vol 5, No 2 (2025) - Team, Editorial (Universitas Syiah Kuala, 2025)
Vol 5, No 2 (2025): Bull. Community. Serv.